2010
DOI: 10.1037/a0019476
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitating patients with left spatial neglect by prism exposure during a visuomotor activity.

Abstract: Daily life visuomotor activities, associated with prism exposure, are a useful tool for rehabilitating USN patients. This new treatment may widen the compliance with prism exposure treatments and their feasibility within home-based programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 88 publications
(122 reference statements)
5
119
0
4
Order By: Relevance
“…Fifteen additional RCTs investigating neglect were found that were not included in those reviews (prism adaptation, 2; virtual reality, 2; limb activation, 2; neck vibration with prism adaptation, 1; visual scanning with limb activation, 1; mental practice, 1; repetitive transcranial magnetic stimulation, 4; and optokinetic stimulation, 2). [471][472][473][474][475][476][477][478][479][480][481][482][483] There is evidence for the efficacy of several top-down and bottom-up approaches in improving both immediate performance and long-term performance on standard neglect tests such as cancellation tests and line bisection tests. * These include half-field eye patching, visual scanning training, prism adaptation, limb activation, optokinetic stimulation, mental imagery (but see the work by Welfringer and colleagues 482 ), and brain stimulation with repetitive transcranial magnetic stimulation, theta burst transcranial magnetic stimulation, or tDCS.…”
Section: Hemispatial Neglect or Hemi-inattentionmentioning
confidence: 99%
“…Fifteen additional RCTs investigating neglect were found that were not included in those reviews (prism adaptation, 2; virtual reality, 2; limb activation, 2; neck vibration with prism adaptation, 1; visual scanning with limb activation, 1; mental practice, 1; repetitive transcranial magnetic stimulation, 4; and optokinetic stimulation, 2). [471][472][473][474][475][476][477][478][479][480][481][482][483] There is evidence for the efficacy of several top-down and bottom-up approaches in improving both immediate performance and long-term performance on standard neglect tests such as cancellation tests and line bisection tests. * These include half-field eye patching, visual scanning training, prism adaptation, limb activation, optokinetic stimulation, mental imagery (but see the work by Welfringer and colleagues 482 ), and brain stimulation with repetitive transcranial magnetic stimulation, theta burst transcranial magnetic stimulation, or tDCS.…”
Section: Hemispatial Neglect or Hemi-inattentionmentioning
confidence: 99%
“…The neuropsychological assessment showed left spatial neglect (table 1), with perseveration behavior. 10 Personal neglect was mild, as assessed by tasks verbally requiring to reach, with the right hand, the left hand and other left-sided body parts, 11,12 and by a task requiring to search targets located on the body, 13 when blindfolded. P1, spontaneously and repeatedly, stated that her left hand belonged to her son, obdurately denying it was her own, while ownership of the remaining part of the left upper limb was preserved (table 2A).…”
Section: Participantsmentioning
confidence: 99%
“…neurologically unimpaired participants (Fortis et al, 2010), matched for age (M = 72.2, SD ± 5.16, range 65-83), and years of education (M = 9.5, SD ± 4.48, range 5-18) was Ă€1.21% (SD ± 3.48, range Ă€16.2% to +6.2%). (e) Complex figure drawing (Gainotti, Messerli, & Tissot, 1972).…”
Section: Baseline Neuropsychological Assessmentmentioning
confidence: 99%